Symposium 3: Re-presencing the digital trace in networked learning design - Goetz, Greta (Proceedings of the International Conference on Networked Learning, 2024)
Recent work in and on networked learning outlines the value in taking a relational view of complex assemblages of people and things such that, for example, non-human entities can be both/either learner and/or teacher. The sociomaterialist perspective brings questions of how power remains continuous yet transformed when the social reach of digital technology is accelerating towards a “tipping point” (Schwab & Malleret 2020). This paper will continue the Freirean work of e-quality set out by networked learning’s founders through a transdisciplinary pattern-design learning approach capable of reflexively tracing macro-level technological, scientific, and social constructs and micro-level experience. This will be elaborated through phenomenological hermeneutic design imitative of how we generate or are traced and influenced by digital traces, seeking to ‘re-presence’ (cf. van Loon in Johnson 2020) the digital trace as it plays out across extended systems while making care-ful use of the digital tool. Theory will draw on Ricoeur’s work on the trace and Stiegler’s concept of the recorded mark. Models of how to re-presence and leave further traces in technology enhanced networked learning design will draw on emergent co-creative knowledge networks also employing care-fully chosen digital tools, including Stiegler’s hermeneutic web, community wikis, and digital gardens with the goal to augment that which is “valued in the rest of life” (Goodyear & Retalis 2010).